Exploration of Moral and Spiritual Development in Education: A Qualitative Study - Nugroho Yogi Suseno; Dwi Maryono; Dwi Esti Wardani (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan)
This study describes the results of a qualitative research on the exploration of moral and spiritual development in Vocational High Schools in Surakarta and how the integration of spiritual components in the curriculum can influence students' character development. Through a participatory observation approach and in-depth interviews, the research highlights the school's commitment to students' character development through prayer, Religious Education subjects, and religious activities. Prayer is identified as the primary means to build students' spiritual connections, while Religious Education is designed to stimulate personal reflection and interfaith tolerance. Students' participation in religious activities is considered an integral element in shaping moral and spiritual character. The discussion covers the importance of integrating spiritual components into the curriculum, the role of teachers, challenges, and recommendations for improvement. The research findings provide deep insights into the school's efforts to shape students' characters holistically, laying the foundation for the development of more effective moral and spiritual education.